Feasibility and Effectiveness of Telephone-Based Telephysiotherapy for Treatment of Pain in Low-Resource Setting: A Retrospective Pre-Post Design. (8th May 2020) - Adhikari, Shambhu P.; Shrestha, Pragya; Dev, Rubee
Abstract : Introduction . Telephysiotherapy (TPT) is a provision of physiotherapy services at a distance, using telecommunication technology when an in-person visit is not a feasible option. The objective of this study was to investigate the effectiveness of TPT in management of pain caused due to various problems among patients living in rural areas of a developing country. Methods . This retrospective study conducted in rural areas of Nepal recruited all patients who met the eligibility criteria during a day campaign. Two physiotherapists, one for assessment and another for treatment, were involved. Based on pretraining assessment finding, evidence-based individualized physiotherapy was prescribed. Pamphlets containing pictures of the prescribed exercises and instructions in the Nepali language were distributed. The treating physiotherapist made telephone calls to every patient each week to give necessary information, correction, modification, and progression of the exercise whatever required. At the end of the second and fourth weeks, pain was assessed using the Numeric Pain Rating Scale (NPRS) through telephone calls. The data were analyzed using ANOVA with repeated measures followed by pairwise comparisons. Results . Fifteen patients having pain due to various conditions participated in the study. The NPRS demonstrated significantly decreased pain (at rest: F  = 3.5, p = 0.04, when worst: F  = 26.4, p < 0.001, during activities of daily living: F  = 16.6, p < 0.001, and during occupation: F  = 15.6, p = 0.001 ) across time. The result met the minimal clinically important difference of NPRS, which is 2. Conclusions . The telephone-based TPT interventions demonstrated significant reduction in pain caused by various musculoskeletal problems. It could be a feasible and effective treatment option for the patients living in rural areas. However, we recommend for large-scale trials to establish effectiveness of the intervention and for its implication into routine clinical practice.